2019
DOI: 10.1111/bph.14887
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II does not regulate nitrite‐dependent nitric oxide formation and vasodilation

Abstract: Background and purpose Although it has been reported that bovine carbonic anhydrase CAII is capable of generating NO from nitrite, the function and mechanism of CAII in nitrite‐dependent NO formation and vascular responses remain controversial. We tested the hypothesis that CAII catalyses NO formation from nitrite and contributes to nitrite‐dependent inhibition of platelet activation and vasodilation. Experiment approach The role of CAII in enzymatic NO generation was investigated by measuring NO formation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
(121 reference statements)
0
13
0
Order By: Relevance
“…[ 51,52 ] The MW of these hCA isoenzymes was computed by this method as well as with the SynGene imaging tool, which was approximately 29 kDa. [ 53 ] The esterase activity of the hCA isoforms was determined by following the change in absorbance at 348 nm over 3 min [ 54 ] according to the method described by Verpoorte et al [ 55 ] One enzyme unit (EU) was defined as the hydrolysis of 1.0 µmol 4‐nitrophenyl acetate to 4‐nitrophenyl per minute at pH 7.4 and temperature 25°C. AAZ (C 4 H 6 N 4 O 3 S 2 , N ‐(5‐sulfamoyl‐1,3,4‐thiadiazol‐2‐yl)acetamide, PHR1908) was used as the reference drug.…”
Section: Methodsmentioning
confidence: 99%
“…[ 51,52 ] The MW of these hCA isoenzymes was computed by this method as well as with the SynGene imaging tool, which was approximately 29 kDa. [ 53 ] The esterase activity of the hCA isoforms was determined by following the change in absorbance at 348 nm over 3 min [ 54 ] according to the method described by Verpoorte et al [ 55 ] One enzyme unit (EU) was defined as the hydrolysis of 1.0 µmol 4‐nitrophenyl acetate to 4‐nitrophenyl per minute at pH 7.4 and temperature 25°C. AAZ (C 4 H 6 N 4 O 3 S 2 , N ‐(5‐sulfamoyl‐1,3,4‐thiadiazol‐2‐yl)acetamide, PHR1908) was used as the reference drug.…”
Section: Methodsmentioning
confidence: 99%
“…Both CA1 and CA2 are expressed in platelets in a relatively high level (2500 and 36,100 copies/platelet respectively) [ 84 ]; however, it is not clear whether platelet CA can reduce nitrite to NO. sGC is strongly activated in washed human platelets incubated with recombinant bovine CA2 together with nitrite [ 83 ], whereas others showed that human, bovine, or mouse CA2 does not regulate nitrite-dependent NO formation in blood [ 85 ]. Recently in experiments with washed human platelets, we showed that cysteine is required for nitrite-dependent sGC activation, which was independent from CA inhibitor [ 86 ], but this assumption needs future experimental confirmations.…”
Section: Nitrate/nitrite/no Pathwaymentioning
confidence: 99%
“…A sophisticated animal study was performed by Wang et al 14 . In CA II þ/þ , CA II ± and CA II -/mice (26 À 32 g body weight), infusion of NaNO 2 (30, 50, 100, 500, 2500 nmol over 5 min corresponding to doses of up to 3.8 mg nitrite/kg body weight) lowered mean arterial blood pressure equally from about 70 mmHg down to 40 mmHg in CA II þ/þ , CA II ± and CA II -/-, suggesting a mechanism independent of CA II 14 . Unfortunately, the authors did not report on the possible formation of S-nitrosothiols, which could have been an indication of hCA II involvement.…”
Section: Potential Nitrite-dependent Physiological and Pharmacological Roles Of Carbonic Anhydrasementioning
confidence: 99%
“…There are contradictory reports in the literature regarding the above mentioned newest CA II activities and even a disputation of a physiological role of CA II in the bioactivation of nitrite [11][12][13][14] . Here, we provide new experimental data in support of the nitrous anhydrase activity of CA II.…”
Section: Introductionmentioning
confidence: 99%